On quasiperiodic solutions of the modified Kadomtsev–Petviashvili hierarchy. (November 2019) - Zhao, Peng; Fan, Engui
Abstract: In this paper, we present the construction of quasiperiodic solutions of the p th equation in the modified Kadomtsev–Petviashvili hierarchy by seeking compatible solutions of the 1th and the p th equations in the derivative nonlinear Schrödinger hierarchy.